2020
DOI: 10.3390/molecules25194440
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium, Iron, Zinc, Copper and Selenium Status in Attention-Deficit/Hyperactivity Disorder (ADHD)

Abstract: In this study, we critically review the literature concerning the relation of Mg, Fe, Zn, Cu and Se and attention-deficit/hyperactivity disorder (ADHD). Elemental status is estimated using peripheral blood parameters, hair, urine, daily intake and response to supplementation. The observed associations between concentration levels of the elements Mg, Fe, Zn, Cu and Se and ADHD symptoms are contradictory. This is partly due to the heterogeneity and complexity of the disorder. As a trend, lower ferritin and zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 146 publications
0
33
0
1
Order By: Relevance
“…Based on the results obtained in this systematic review, the specific role of dietary nutrients with zinc and iron still seems controversial for the treatment of ADHD, being most consistent with the evidence for zinc. Moreover, although the reviewed studies found a relationship between the use of dietary supplements containing these elements with the improvement of ADHD symptoms, neither the mono-causal role of a concrete specific nutritional deficiency among ADHD children nor the role of a concrete dietary nutrient in the management of this disorder were proven (as was reported quite recently [56]). Future controlled clinical trials are needed, examining the efficacy of mineral supplementation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on the results obtained in this systematic review, the specific role of dietary nutrients with zinc and iron still seems controversial for the treatment of ADHD, being most consistent with the evidence for zinc. Moreover, although the reviewed studies found a relationship between the use of dietary supplements containing these elements with the improvement of ADHD symptoms, neither the mono-causal role of a concrete specific nutritional deficiency among ADHD children nor the role of a concrete dietary nutrient in the management of this disorder were proven (as was reported quite recently [56]). Future controlled clinical trials are needed, examining the efficacy of mineral supplementation.…”
Section: Discussionmentioning
confidence: 90%
“…Iron is a cofactor mineral that systematizes the production of dopamine and norepinephrine, an essential element participating in a wide variety of metabolic processes, including oxygen transport, deoxyribonucleic acid synthesis, and electron transport [55]. Some studies have analyzed the contribution of zinc and iron on ADHD occurrence, but conflicting findings have been obtained [56]. As a trend, compared to healthy control groups, lower levels of iron and zinc have been observed in children diagnosed with ADHD, but it is not clear whether changes in nutrient levels in blood tests mediate treatment outcomes in children with ADHD who consume mineral supplements [57,58], or even what sub-groups could particularly benefit from.…”
Section: Introductionmentioning
confidence: 99%
“…Necrosis, cystic transformation, interstitial focus, and cavernous vacuolation are all possible risk factors for the development of these illnesses and may contribute to the origin of ADHD in children [ 19 ]. Studies on children have reported increased serum copper levels, as evidenced by higher hair copper levels [ 20 , 21 ]. Our study, however, estimated an increase in the hair and urinary copper levels in the ADHD group.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на отмеченную нами ранее взаимосвязь между нарушениями обмена цинка и меди с наличием СДВГ у детей, в настоящем исследовании значимых отличий данных показателей от контрольных выявлено не было. Это обстоя-тельство может быть обусловлено более старшим возрастом обследуемых, а также вариабельностью маркеров элементного статуса у детей с СДВГ (Robberecht et al, 2020).…”
Section: микроэлементы в медицине: оригинальные статьиunclassified